Theories of learning/by Ernest R. Hilgard and Gordon H. Bower - "Hilgard, Ernest R." (New York, 1966)
Learning is a central topic within American psychology, and its problems have provided the occasion for hundreds of experimental studies. The science of learning remains in a state of flux, in part because we have not yet reached agreement upon the most appropriate concepts to use in stating our problems and in interpreting our data. This book represents an attempt to provide in one place an introduction to the major theories of learning which are current among psychologists doing research in this important field of study. The aim is to see theory in relation to experiment. Each of the several theories is therefore illustrated by a selected topic within the field of experimentation.
Keywords: "Learning, Psychology"